Research and study paths in physics and mathematics in secondary schools - Gazzola, María Paz; Otero, María Rita; Llanos, Viviana Carolina (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This article reports the results of a research project aimed at developing, analyzing, andevaluating genuinely co-disciplinary research and study paths [RSP] in secondary schools.The implementation and analysis of an RSP in physics and mathematics is presented. Theinstrument was implemented in five regular mathematics classes in different schools inthe district of Tandil, Argentina. A total of 116 students between 16 and 18 years of agetook part. The anthropological theory of the didactic, the RSP theoretical concepts, andthe Herbartian schema are used as theoretical referents. This article describes and analyzesin detail the generation process of the didactic environment—mesogenesis—in eachimplementation. The obtained results allow the identification of difficulties in organizingand developing a study environment in the classroom as proposed strictu sensu in an RSP.The analysis of mesogenesis allows deducing some conclusions about the ecology of thistype of teaching in regular secondary school courses.